2004
DOI: 10.1124/mol.104.004978
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Binding of Folates and Antifolates to Brush-Border Membrane Vesicles Isolated from Human Kidney

Abstract: Antifolates such as methotrexate, raltitrexed, and pemetrexed are among the most effective and widely used anticancer drugs. The antifolates are also among the most unpredictable of anticancer drugs with respect to pharmacokinetics and toxicity. In this study, we assessed the binding of folates and antifolates to the folate receptors (FRs) of human proximal tubules and the effects of pH on binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…12 Folates and antifolates are reabsorbed at kidney proximal tubules via folate receptors and transported into cells. [13][14][15] We hypothesize that the accumulation of the drug intracellularly and the subsequent inhibition of purine and protein synthesis, result in tubular cytotoxicity and possibly secondary tubulointerstitial inflammation leading to AKI. Our patient did not respond to corticosteroid treatment.…”
mentioning
confidence: 99%
“…12 Folates and antifolates are reabsorbed at kidney proximal tubules via folate receptors and transported into cells. [13][14][15] We hypothesize that the accumulation of the drug intracellularly and the subsequent inhibition of purine and protein synthesis, result in tubular cytotoxicity and possibly secondary tubulointerstitial inflammation leading to AKI. Our patient did not respond to corticosteroid treatment.…”
mentioning
confidence: 99%
“…13,14) It has been found that these carriers are pH-sensitive and are expressed not only in the intestine but also in other organs, including the placenta. [15][16][17] Furthermore, it is possible that intracellular accumulation of folates reflects the operation of outward transport mediated by members of the family of ATP-binding cassette transporters, such as MRPs and breast cancer resistance protein (BCRP/ ABCG2). 18) It is known that the placenta is an organ that develops in a short period of time, and that its functions change with the progress of gestation.…”
mentioning
confidence: 99%
“…Moreover, a proximal tubular damage, even if mild, as demonstrated in an experimental study published in 2005 (7), could increase drug nephrotoxicity, since the proximal tubule is the site where folic acid is reabsorbed through FR-α and RFC carriers. Besides, folate absorption is increased by an acidic environment, and decreased by a high urine flow, meaning that fluid and alkaline solutions administration could augment folate excretion, and as a consequence reduce its protective effects.…”
Section: Discussionmentioning
confidence: 99%